Outcome in body-contouring surgery after massive weight loss: A prospective matched single-blind study. Issue 10 (October 2015) - Tremp, Mathias; Delko, Tarik; Kraljević, Marko; Zingg, Urs; Rieger, Ulrich M.; Haug, Martin; Kalbermatten, Daniel F.
Summary Introduction Body-contouring (BC) procedures after massive weight loss (MWL) are extensive and numerous. Currently, inconsistent data exist regarding quality-of-life (QoL) scales, and long-term analysis is lacking. The aim of this study was to investigate the long-term outcome of patients who elect to have BC procedures after MWL. Methods Post-bariatric patients and patients who had dietary weight loss with no history of bariatric surgery (BS) (BC group) were included. Patients after BS with similar demographic characteristics but no BC procedures served as the control group (BS group). The results were compared with severely obese patients who have not yet undergone BS or BC surgery (obese group). Outcome measures include the type of BC surgery with the rates of the associated procedures and outcome satisfaction evaluated after the Moorehead–Ardelt questionnaire (range −3.0 to +3.0). Results Fifty-six female and 10 male Caucasian patients with a mean age of 50 years (14 years) who underwent BC procedures between February 1999 and October 2009 were included. Of those, 23 patients completed the survey in 2014 (20 female and three male patients, mean age of 53 years (14 years)) at a final follow-up of 8 years (3 years). Two years (range 1–3 years) after MWL, a total of 51 BC procedures were performed. The most frequent interventions were abdominoplasty (n = 20), followed by rectus plication and liposuction (n = 7 and n = 6, respectively). QoL scores revealed a high overall patient satisfaction in the BC group, which was comparable with the BS group (n = 23). The obese group (n = 17) had a significantly lower overall QoL and lower health-related QoL (HRQoL) subdomains compared with the BC and BS group. Conclusion BC procedures lead to high and durable patient satisfaction. However, the appropriate management of expectations before surgery is mandatory.